Perceptions of the educational environment at entry and exit of medical students to clinical teaching in a rural medical college - James, Deepsha; Mani, Susan; Mathew, Anna; Velusamy, Saravana Kumar (International Journal of Research in Medical Sciences, 2017)
Background: The foundation for good health care to patients is the competence of health care providers. Motivated learners in supportive environments have high levels of self-efficacy. DREEM is considered a valid and reliable tool, globally accepted for assessing the educational environment. The objectives of the study were to elicit the perceptions of first clinical year and final year medical students in a rural medical college using the Dundee ready education environment measure (DREEM) inventory and to find out if there is any difference in the perceptions at entry and exit to the clinical environment. Methods: This was a cross sectional study on 78 students each in first clinical year and final year of this rural medical college. The DREEM inventory was used by the investigator to record relevant data, which was then statistically analyzed using SPSS software. The student t-test was used to compare the total and sub-domain mean scores in the two groups. Results: There was significant difference in perception in the final year students compared to the first clinical year class. Conclusions: The students of both first clinical year and final year have a positive perception about their educational environment. However there is a significant difference in the total DREEM score as well as total sub-domain scores among first clinical year students and final year students. Student perceptions are a valuable resource for institutional curriculum planners to make appropriate changes to enhance student learning.